Sustainable and Inclusive Educational Spaces: Interior Design Approaches Supporting Gender Equality in the GCC - Almurbati, Nehal (Journal of Cultural Analysis and Social Change, 2026)
Educational facilities play a critical role in fostering inclusive learning environments and supporting the United Nations’ Sustainable Development Goal 5 (SDG 5), which aims to achieve gender equality and empower all women and girls. Yet, the design of these spaces frequently overlooks gender-responsive considerations, especially regarding the unique cultural, religious, and social needs of Muslim women and women from the Gulf Cooperation Council (GCC) region. This study examines how interior design proposals can enhance the experiences of Muslim and GCC women in educational settings, utilising a visual analysis of selected case studies and projects. By rigorously examining spatial organisation, materiality, and design choices through a gender-sensitive lens, the research specifically explores how safety, privacy, comfort, and spaces for cultural practices are addressed—issues that are central to SDG 5’s pursuit of equitable participation and well-being. Contributions from 40 female and 3 males interior designers are analysed, situating their work within broader debates on inclusivity and the right to equitable educational space for Muslim and GCC women. The findings generate insights into gender- and culture-specific spatial needs and inform targeted design recommendations that advance both supportive and equitable educational facilities. This research, therefore, contributes directly to the discourse and practical realisation of gender-responsive design for educational environments, and aligns with the vital goals of SDG 5 to create spaces in which all women, especially those from Muslim and GCC backgrounds, can thrive.